The teaching of unconventional sports at school from a teaching perspective: a case study (Research, Society and Development, 2023)
The objective of the study was to investigate the perception of teachers about non-conventional national sports in a school in Macapá-AP. In the methodological aspect, the research was characterized as a case study with a qualitative approach. The research steps were organized in three moments: signature of the TCLE by the professors, signature of the Term of Consent by the coordination and data collection with the professors. Seven sports were selected for the field research and the sample consisted of two high school teachers who answered a questionnaire about unconventional Brazilian sports. The results revealed that the professors know some sports created in Brazil, but still know little about the seven modalities selected in the research. The teaching of unconventional sports at school is a concrete possibility, considering that some sports can be performed in small spaces, with materials that can be made by teachers and some have technical gestures that are easy to perform. Thus, the study concludes that teaching non-conventional sports at school is still an expanding theme, which makes it necessary to carry out more studies within the educational environment.